2016
DOI: 10.5713/ajas.15.0886
|View full text |Cite
|
Sign up to set email alerts
|

Performance Responses, Nutrient Digestibility, Blood Characteristics, and Measures of Gastrointestinal Health in Weanling Pigs Fed Protease Enzyme

Abstract: Although exogenous protease enzymes have been used in poultry diets quite extensively, this has not been the case for pig diets. In general, due to their better gut fermentative capacity and longer transit time, pigs have greater capacity to digest dietary proteins than poultry. However, in early-weaned piglets, the stress brought about by weaning adversely affects the digestion of dietary proteins. Therefore, a study was conducted to determine the effects of a commercial protease enzyme in weanling pigs. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 20 publications
(27 reference statements)
5
49
1
6
Order By: Relevance
“…In present study, adding protease to the diet increased ADG and G: F ratio only during phase 3 of post-weaned and growing pigs. In agreement with our results, Tactacan et al (2016) and Wang et al (2011) reported that the ADG and G:F ratio were increased in weaned pigs fed diets containing protease. This may be attributable to the supplementation of exogenous protease enzyme could increase the hydrolysis of protein and stimulate the synthesis of digestive enzymes in post-weaned pigs, could alter intestinal morphological which was damaged by weaning, and could eliminate the antinutritional factors of feedstuffs, therefore, resulting in better digestion and improving growth performance in weaned pigs (Hedemann and Jensen 2004;Fru-Nji et al 2011;Yang et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In present study, adding protease to the diet increased ADG and G: F ratio only during phase 3 of post-weaned and growing pigs. In agreement with our results, Tactacan et al (2016) and Wang et al (2011) reported that the ADG and G:F ratio were increased in weaned pigs fed diets containing protease. This may be attributable to the supplementation of exogenous protease enzyme could increase the hydrolysis of protein and stimulate the synthesis of digestive enzymes in post-weaned pigs, could alter intestinal morphological which was damaged by weaning, and could eliminate the antinutritional factors of feedstuffs, therefore, resulting in better digestion and improving growth performance in weaned pigs (Hedemann and Jensen 2004;Fru-Nji et al 2011;Yang et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Protease, as stand-alone enzyme or as a part of enzyme cocktails, has shown positive effects on growth performance and nutrient digestibility to pigs (Jo et al 2012;Zuo et al 2015;Tactacan et al 2016). However, to date, most of the studies on protease have been generated from enzyme cocktails, no enough data about the supplementation of Bacillus licheniformis derived-protease in post-weaned and growing pigs.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of DM digestibility, protease diet has a trend for linearly increasing in the current study. This is similar with the findings of Tactacan, Cho, Cho, and Kim (), which reported that the ATTD of DM and N was increased in pigs fed the protease diet on 21 days and 42 days compared with pigs fed the control diet. Meanwhile, due to the difference in ingredients, age of pigs and enzyme products, the effectiveness of supplying protease in pig diets may be different.…”
Section: Resultssupporting
confidence: 91%
“…It also resulted in improved AID of some indispensable amino acids, nutrients (Pan et al, 2016), crude protein and standardized ileal digestibility (Yu et al, 2016). Other studies confirmed that weaned pigs fed protease supplemented diets improved nutrient digestibility and growth performance ( Zuo et al, 2015;Tactacan et al, 2016). Some studies of growing or finishing pigs did not confirm positive effects of protease on growth performance, although its inclusion in diets improved AID of amino acids, gross energy (O'Shea et al, 2014) and faecal nitrogen digestibility (Mc Alpine et al, 2012a) when diets were based on wheat distillers and rapeseed meal.…”
Section: Resultsmentioning
confidence: 50%